The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1107/s0567740876004913
|View full text |Cite
|
Sign up to set email alerts
|

Die Kristallstruktur von L.T.-GeS2

Abstract: the computations were carried out on the FACOM 270--30 computer at this Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 2 publications
(2 reference statements)
4
77
0
1
Order By: Relevance
“…[5] Prewitt and Young reported a dense high-temperature and high-pressure g-GeS 2 structure in which GeS 4 units are connected in a threedimensional tetragonal cristobalite-related network (space group I4 Å 2d). [6] Moreover, Viaene and Moh reported a highpressure/high-temperature (g) form of GeS 2 that is stable above 3000 bar at 600 8C and can be quenched to give a metastable phase at room temperature.…”
mentioning
confidence: 99%
“…[5] Prewitt and Young reported a dense high-temperature and high-pressure g-GeS 2 structure in which GeS 4 units are connected in a threedimensional tetragonal cristobalite-related network (space group I4 Å 2d). [6] Moreover, Viaene and Moh reported a highpressure/high-temperature (g) form of GeS 2 that is stable above 3000 bar at 600 8C and can be quenched to give a metastable phase at room temperature.…”
mentioning
confidence: 99%
“…It has been reported that α-GeS 2 crystals have a GeS 4 tetrahedral network based on a monoclinic system (space group: Pc) [11]. Therefore, judging from the existence of the NBS atoms, the GeS 4 tetrahedral network was partially broken by mixing with Li 2 S during MA.…”
Section: Resultsmentioning
confidence: 99%
“…To assess N Ge-S , W Ge-S was obtained from a least-squares fit using two Gaussian curves for the Ge-NBS and Ge-BS correlations. It is well known that the Ge-NBS correlation length, l Ge-NBS , is relatively shorter than the Ge-BS correlation length, l Ge-BS , in a GeS 4 tetrahedron in α-GeS 2 crystals [11]. Therefore, the first peak for the Ge-S correlation was fitted using two Gaussian curves for the Ge-NBS and Ge-BS correlations.…”
mentioning
confidence: 99%
“…GeS 2 has two types of crystal structure. One is two-dimensional GeS 2 which is composed of corner-sharing GeS 4 tetrahedra cross-linked by edge-sharing tetrahedra and usually obtained at a relatively high temperature [7], and the other is three-dimensional GeS 2 crystal composed of corner-sharing GeS 4 tetrahedra with the same local structure as SiO 2 [8].…”
Section: Resultsmentioning
confidence: 99%